Differences in open innovation practices between headquarters and subsidiaries in the automotive industry: The French case. Issue 1 (1st January 2019) - Martins, Marina Borges; Kaminski, Paulo Carlos
Abstract: Open Innovation (OI) is a growing trend as a practice to improve the Product Development Process (PDP). It is changing the way companies create new products and technology. The automotive industry is not an exception to that trend. This industry began to implement this concept many years ago but not in a homogeneous way. Now, more than ever, innovation is playing a vital role in this industry due to the technological revolution it is facing, and new innovation tools are needed. This study aims to compare OI practices in the PDP of French companies at their headquarters and at their subsidiaries located in Brazil. It presents multiple case studies based on interviews with experienced professionals from four different companies. Public documents were also used in the analysis of the innovation process in these companies. A literature review of PDP and OI is presented to ground the questions that guided these interviews. This study reveals that, in addition to stronger technology development, headquarters in France have more structured OI practices than subsidiaries in Brazil. It was found that automakers in Brazil perform some OI practices while suppliers have few to no product development. Furthermore, in both countries and industries, outside-in OI practices are much more common than inside-out ones.